Polystyrene with Persistently Enhanced Fluorescence: Photo‐Induced Atom Transfer Radical Polymerization Using a Pyrene‐Based Initiator. Issue 11 (15th July 2019) - Su, Chun‐Hsien; Wu, Zhenqiang; Lin, Ching‐Kai; Han, Hui‐An; Chen, Yi‐An; Chou, Pi‐Tai; Fu, Xuefeng; Peng, Chi‐How
Abstract: The pyrene‐based atom transfer radical polymerization (ATRP) initiator of 1‐pyrenemethyl 2‐bromoisobutyrate (PMBriB) was applied to the photo‐induced radical polymerization of methyl acrylate, methyl methacrylate, and styrene. During the polymerization, the fluorescence of the polymer solution caused by the chain end pyrene group was observed to be slightly enhanced in all cases, possibly due to the decline of the aggregation caused quenching (ACQ) effect. However, the fluorescence of polystyrene obtained from photo‐induced ATRP was significantly increased. Differential scanning calorimeter (DSC) measurements, NMR spectroscopy, and fluorescence measurements associated with a series of control studies demonstrated that the enhanced fluorescence was a persistent phenomenon in both solution and the solid state but the polystyrenes with and without enhanced fluorescence showed no observable difference in chemical bonding and molecular conformation. At this stage, the coexistence of pyrene, 2‐bromoisobutyrate group, styrene, and light was required for this novel phenomenon and the mechanism of this fluorescence enhancement is still being studied. Abstract : Shine bright : The pyrene‐based initiator 1‐pyrenemethyl‐2‐bromoisobutyrate (PMBriB) is employed in the photo‐induced atom transfer radical polymerization (ATRP) of methyl acrylate, methyl methacrylate, and styrene. All polymerizations show slightly increased fluorescence, with the exception of the photo‐induced ATRP of styrene, which demonstrates a highly enhanced fluorescence. The coexistence of pyrene, the 2‐bromoisobutyrate group, styrene, and light is required for this phenomenon.